1996
DOI: 10.1055/s-2006-957810
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the Essential Oil ofAchillea wilhelmsiifrom Iran

Abstract: Constituents of the essential oil of Achillea wilhelmsii L. growing wild in Kerman-Iran were studied by TLC, GC, and GC/MS methods. The main components of the monoterpene fraction of the oil were camphor, borneol, linalool, 1,8-cineole, chrysanthenol acetate, and carvacrol. The percentage of the identified sesquiterpenoid components was relatively high and constituted 29% of the oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…The reports indicated that the A. wilhelmsii essential oil also contains active components (Afsharypuor et al, 1996) with different biological properties such as anxiolytic (Majnooni et al, 2013), insecticide (Khani et al, 2012), cytotoxic, and anthelmintic potential (Ali et al, 2011). Our recent study indicated the in vitro antioxidant activity of A. wilhelmsii essential oils with the p-cymene, terpinolene, and a-thujene as the major compounds (Roshanaei et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…The reports indicated that the A. wilhelmsii essential oil also contains active components (Afsharypuor et al, 1996) with different biological properties such as anxiolytic (Majnooni et al, 2013), insecticide (Khani et al, 2012), cytotoxic, and anthelmintic potential (Ali et al, 2011). Our recent study indicated the in vitro antioxidant activity of A. wilhelmsii essential oils with the p-cymene, terpinolene, and a-thujene as the major compounds (Roshanaei et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…Our results showed that the main constitute in the essential oil of the flower and stem of Achillea wilhelmsii from Taftan area were camphor with 34.49% in the leaves and stems, and 27.99% in the flowers. Another study on the plant which performed in Mazandaran province showed that the major components of the essential oil of the leaves and flowers of A. wilhelmsii were camphor with 24.1% and 21.2% respectively (18).Where as the amount of this component in the plant which collected from Kerman was 9.0% and in the plant from Kazeroon in Fars province was 2.2% (17,19). The main constitute of the oil of A. wilhelmsii from Kazeroon was carvacrol (25.1%), while the main component in the oil of the plant from Kerman was caryophyllene oxide (12.5%).…”
Section: Discussionmentioning
confidence: 99%
“…To date Achillea wilhelmsii has been analyzed from different parts of Iran such as Fars (17), Mazandran (18) and Kerman (19) for both the composition of essential oil and different pharmacological properties. But there are no reports of such an analysis on Achillea wilhelmsii from Taftan area in Sistan and Baluchestan, which is an important geographical zone for medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study camphor was not detected as a headspace constituent of A. tenuifolia collected from Isfahan province, but was found in other species. Afsharypuor et al [7,8] [36] reported that sabinene was dominant in the essential oil of one of the two populations of A. millefolium collected in Spain.…”
Section: Gc/ms Analysismentioning
confidence: 99%
“…Many species of Achillea have been analyzed for their bioactives with more than 100 components found, including volatiles (mono-and sesquiterpenes or their lactones) in headspace vapor or essential oils and highermolecular-weight phenolics or flavonoids from the extracts ( [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]). …”
Section: Introductionmentioning
confidence: 99%